2018
DOI: 10.1016/j.jcmg.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Native T1 Mapping and Extracellular Volume Mapping for the Assessment of Diffuse Myocardial Fibrosis in Dilated Cardiomyopathy

Abstract: Native T1 exhibited comparable ability as ECV measurement in the detection and quantification of histological collagen volume fraction, with high reproducibility, and therefore diffuse myocardial fibrosis in DCM may be reliably assessed by native T1 mapping without the administration of gadolinium contrast agent. In addition, cardiac magnetic resonance-derived ECV showed excellent agreement with histological extracellular space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
111
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(132 citation statements)
references
References 32 publications
2
111
2
3
Order By: Relevance
“…Additionally, reproducibility of ECV was not appraised in this study due to the small study sample. Nevertheless, previous studies have observed an excellent inter-reader and inter-system reproducibility of ECV measurements (32).…”
Section: Discussionmentioning
confidence: 89%
“…Additionally, reproducibility of ECV was not appraised in this study due to the small study sample. Nevertheless, previous studies have observed an excellent inter-reader and inter-system reproducibility of ECV measurements (32).…”
Section: Discussionmentioning
confidence: 89%
“…Recently, extracellular volume fraction (ECV) quantification by CMR T1 mapping technique has been introduced to evaluate DMF in vivo. Previous studies demonstrated that ECV reliably reflect the degree of DMF and, more importantly, is associated with prognosis in various cardiac diseases [12][13][14]. Thus, in this study, we hypothesized that myocardium in liver cirrhosis has structural alterations such as DMF, which could be effectively addressed by CMR.…”
Section: Introductionmentioning
confidence: 89%
“…CMR is best suited for this purpose with its unique ability to characterise myocardial tissues. LGE represents irreversible replacement fibrosis, while ECV represents reversible DMF [10,13]. As myocardial fibrosis is associated with cardiac hypertrophy and a stiff, noncompliant LV [38], application of these two novel CMR techniques is clinically relevant for the indirect assessment of LV compliance or diastolic property.…”
Section: Myocardial Structural Alterations In Cirrhosismentioning
confidence: 99%
“…Historically, diffuse myocardial fibrosis has been difficult to detect without the inherent risks attached to invasive cardiac biopsy. However, the advent of native myocardial T1 mapping and ECV techniques by CMR now permit the quantification of diffuse fibrosis non-invasively (27) with excellent reproducibility and robust validation against biopsy-proven collagen volume fraction and extracellular space reported in explanted hearts (28) and biopsied patients with dilated cardiomyopathy (29). Two previous studies of anthracycline cardiomyopathy in adults have described abnormal elevation of ECV in cancer survivors 3 years 15 In addition, absolute values of native myocardial T1 and ECV correlated significantly with left ventricular volumes and native myocardial T1 also correlated with LVEF, MAPSE and LAVi.…”
Section: Native Myocardial T1 Mappingdiffuse Fibrosismentioning
confidence: 99%